Understanding community disruption in the aftermath of earthquakes: the 2009 L’Aquila and 2016 Amatrice earthquakes in central Italy - D'Errico, Danila (2020)
For many years, the main focus of psychological research related to the impact earthquakes have on individuals has mainly concentrated on the development and prevalence of psychological disorders among survivors, especially PTSD, Anxiety and Depression. However, only a small subset of people actually meets all of the criteria to receive a psychiatric diagnosis.